2018
DOI: 10.1128/microbiolspec.arba-0032-2018
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance inEnterococcusspp. of animal origin

Abstract: Enterococci are natural inhabitants of the intestinal tract in humans and many animals, including food-producing and companion animals. They can easily contaminate the food and the environment, entering the food chain. Moreover, is an important opportunistic pathogen, especially the species and , causing a wide variety of infections. This microorganism not only contains intrinsic resistance mechanisms to several antimicrobial agents, but also has the capacity to acquire new mechanisms of antimicrobial resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
173
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(200 citation statements)
references
References 366 publications
8
173
1
5
Order By: Relevance
“…If our rooting strategy is correct, our results suggest that the animal isolates represent multiple lineages that diverged prior to the emergence of the clinical subclades in the clade A 3 . Importantly, animal-associated branches have significantly lower ampicillin resistance, mutations associated with fluoroquinolone resistance, virulence determinants, and average number of insertion sequences, similar to what has previously reported 41 . Furthermore, the amount of recombination that we found in clade A genomes was greater than previous results.…”
Section: Discussionsupporting
confidence: 81%
“…If our rooting strategy is correct, our results suggest that the animal isolates represent multiple lineages that diverged prior to the emergence of the clinical subclades in the clade A 3 . Importantly, animal-associated branches have significantly lower ampicillin resistance, mutations associated with fluoroquinolone resistance, virulence determinants, and average number of insertion sequences, similar to what has previously reported 41 . Furthermore, the amount of recombination that we found in clade A genomes was greater than previous results.…”
Section: Discussionsupporting
confidence: 81%
“…Using cgMLST indicated that the E. faecalis and the E. faecium isolates belonged to STs typically identified among livestock-associated strains [55]. E. faecium isolated from pigs in this study were represented by a distinct population belonging to ST133.…”
Section: Discussionmentioning
confidence: 60%
“…These findings suggest a limited potential for transmission of VRE between humans and pigs. Similarly, E. faecium ST310, detected in three poultry isolates, is a poultry-adapted ST that is prevalent among broilers in Sweden [59,60], and E. faecium ST13 and ST157 have been reported in poultry in Sweden, Denmark, and Korea [55]. Taken together, MLST analysis did not reveal any close relationship to typical nosocomial strains belonging to CC17, or to recently emerged endemic strains ST203 and ST796.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations